Seguridad e Ideología en Colombia, 1978-1982: análisis crítico del discurso de Julio César Turbay Ayala (2015)
We analyze the concept of security in the discourse of President Julio Cesar Turbay Ayala (1978-1982) in Colombia. That term, seen as a political-military category, is placed in a historical-contextual perspective –local and international– in order to clarify how the representation and socio-cognitive guidance systems were configured, as well as it also analyzes the ambiguity it had. Likewise, we offer an hermeneutical exercise and a descriptive approach, that allows understanding how the relationships between discourse, context and ideology, made it possible to deploy and redesign that term; and how those relationships, in the end, brought a justification several measures in order to restore the order and public moral within the framework of the said National Security.